Մխիթար Գոշի խորհրդածութիւնները մարդկանց նախնական ազատութեան մասին եւ վարդապետաց դասի կայացումը միջնադարեան Հայաստանում - Վարդանեան, Արեգ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В знаменитом «Судебнике» Мхитара Гоша есть следующая, несвойственная церковному иерарху мысль: люди были созданы Богом свободными, но они служат господам по экономическим причинам. В арменистике есть две интерпретации происхождения этой мысли: некоторые связывают это с так называемым «Армянским Ренессансом», другие видят в этой мысли некий «гуманистический гений» Гоша. Суть нашей статьи показать, что это мысль не что иное, как интерпретация стихов 1:26—28 Книги Бытия. Кроме того, мы показываем, что такая интерпретация в некотором отношении отличается от взглядов, дошедших до нас в древнеармянской переводной патристической литературе. В конце статьи мы предлагаем гипотезу о происхождении такого рода мышления в эпоху Мхитара Гоша. In the famous “Lawcode” of Mkhitar Gosh, one encounters a peculiar remark on the original human society. The essence of Gosh’s idea is that people were created free by God, but they serve masters for economic reasons. Traditionally, this idea has been interpreted as evidence of the so-called Armenian Renaissance or, on the contrary, as a reflection of Gosh’s unconventionally humanistic worldview. The purpose of this paper is to show that this idea is derived from Gosh’s interpretation of Genesis 1:26—28. Moreover, it is worth noting that Gosh diverges significantly from the patristic tradition of its interpretation available in his time through classical Armenian translations. As a result, we present a hypothesis about the social origin of Gosh’s idea.
Keywords: Կրօնագիտութիւն